Sistem Penjualan Furnitur Berbasis Web Pada Cv. Ferdiosa - Dafid Ariyanto; Emmy Wahyuningtyas (Informatics Engineering Department-UWKS, 2019)
FERDIOSA one of the companies engaged in the sale of furniture. So far CV.FRDIOSA socialization is still done simply by phone and visits. This is a less effective and efficient way because in addition to requiring a lot of time, it also requires a lot of costs to be incurred. Therefore CV. FERDIOSA should have a growing marketing strategy. For that required an application in the form of a website that is able to provide information about products to customers quickly via the internet. This problem can be overcome with website pembutanulangi as a medium that allows customers in obtaining information about the price, type, image and size of products that are marketed CV. FERDIOSA. With the website, customers can place orders even though the place of sale is very far